Aktivitas Integrated Marketing Communications Terhadap Brand Image Untuk Industri Rokok Kelas Mild - Mohamad Hadi Prasetyo (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
The cigarette industry in Indonesia has evolved from a traditional industry to be one of the important manufacturing sectors in terms of value added, employment and government revenue. On the other hand, aside from increasing social welfare, the government also has a moral responsibility particularly for raising public awareness of their health. Draft of Government Regulation regarding tobacco based-product as an addictive substance expressly prohibits the advertising, promotion and sponsorship of products containing tobacco. In the industry of mild class cigarette, the level of competition gets tighter where many cigarette companies conduct their integrated marketing communication activities in creative ways. This research is aimed at determining the effect of Integrated Marketing Communication variables on Brand Image of mild class cigarette companies in Bandung region. This research type is descriptive and verification research. The method used is survey descriptive method i.e collecting data on the research object by taking a sample of the population. Questionnaires are used as the principal means of collecting data. The positive coefficient shows that there is a positive relationship between the integrated marketing communications with brand image. As t count > t table (7.748> 1.965), H0 is rejected. Thus, it is found that there is a significant influence of integrated marketing communications on brand image.